Comparison of clinical efficacy between autologous partially demineralized dentin matrix and deproteinized bovine bone mineral for bone augmentation in orthodontic patients with alveolar bone deficiency: a randomized controlled clinical trial - Leping Ouyang; Jingwei Li; Yuhang Dong; Jingyu Li; Feifan Jin; Ying Luo; Renfei Wang; Shuhua Wang (BMC, 2024)
Abstract Background It is common to see patients who need orthodontic treatment but with insufficient alveolar bone volume. However, safe and effective tooth movement requires sufficient alveolar bone width and height. The aim of this study is to compare the bone augmentation efficacy of Autologous Partially Demineralized Dentin Matrix (APDDM) and Deproteinized Bovine Bone Mineral (DBBM) in orthodontic patients with insufficient bone by using a randomized controlled clinical trial approach. Materials and methods Twenty-seven orthodontic patients involving 40 posterior teeth alveolar sites (n = 40) with insufficient alveolar bone volume were randomly divided into a control group (n = 20) and an experimental group (n = 20). The patients in the experimental group were treated with APDDM, and those in the control group were treated with DBBM. After surgery, the adjacent teeth are moved toward the bone grafting sites according to the orthodontic treatment plan. Patients completed a postoperative response questionnaire by the Visual Analogue Scale (VAS) score to indicate pain and swelling in the bone grafted area at the time of suture removal; and CBCT scans were conducted before surgery, 6 months and 2 years after surgery to assess changes in buccal and central alveolar heights, as well as widths at the alveolar ridge apex and 3 mm, 5 mm below the apex, respectively. The CBCT image sequences were imported into Mimics 21.0 software in DICOM format. The data of the patients in both groups were collected and analyzed by SPSS 25.0. Results The VAS scores were significantly lower in the APDDM group than in the DBBM group (p < 0.05). Significant increases were observed in alveolar bone height and width at 6 months and 2 years postoperative (p < 0.05); At 2 years, the APDDM group exhibited a reduction in buccal crest height and in 3 mm, 5 mm width below alveolar ridge apex, relative to 6 months (p < 0.05), while the DBBM group showed a decrease only in the central height of the alveolar bone (p < 0.05). There was a significant bone augmentation increase found only 3 mm below the alveolar ridge apex in the APDDM group compared with the DBBM group among all 6 months group comparison (p < 0.05). At 2 years, the augmentation effects were similar across both groups (p > 0.05). Conclusion Radiomics analysis indicates that APDDM serves as a viable bone augmentation material for orthodontic patients with insufficient alveolar bone volume, achieving comparable clinical efficacy to DBBM. Additionally, APDDM is associated with a milder postoperative response than DBBM. The registration number (TRN) ChiCTR2400084607.